Apilimod Inhibits the Production of IL-12 and IL-23 and Reduces Dendritic Cell Infiltration in Psoriasis - Wada, Yumiko; Cardinale, Irma; Khatcherian, Artemis; Chu, John; Kantor, Aaron B.; Gottlieb, Alice B.; Tatsuta, Noriaki; Jacobson, Eric; Barsoum, James; Krueger, James G. (PLOS ONE, 2012)
Psoriasis is characterized by hyperplasia of the epidermis and infiltration of leukocytes into both the dermis and epidermis. IL-23, a key cytokine that induces TH17 cells, has been found to play a critical role in the pathogenesis of psoriasis. Apilimod is a small-molecule compound that selectively suppresses synthesis of IL-12 and IL-23. An open-label clinical study of oral administration of apilimod was conducted in patients with psoriasis. Substantial improvements in histology and clinical measurements were observed in patients receiving 70mg QD. The expression of IL-23p19 and IL-12/IL-23p40 in skin lesions was significantly reduced in this dose group, with a simultaneous increase in IL-10 observed. A decrease in the levels of TH1 and TH17 cytokines/chemokines in skin lesions followed these p19 and p40 changes. In parallel, a reduction in skin-infiltrating CD11c+ dendritic cells and CD3+ T cells was seen, with a greater decrease in the CD11c+ population. This was accompanied by increases in T and B cells, and decreases in neutrophils and eosinophils in the periphery. This study demonstrates the immunomodulatory activity of apilimod and provides clinical evidence supporting the inhibition of IL-12/IL-23 synthesis for the treatment of TH1- and TH17-mediated inflammatory diseases.